16. Healing Process Of Burns (Vulnus combustion) Degrees IIB Using Mixed Leaf (Spondias dulcis F.) Fresh And Dry With Vaselin In Rats (Rattus Norvegicus) - Ummu Balqis; Mirna Safrani Fauzi; Zuhrawati NA; Nazaruddin Nazaruddin; Razali Daud; Abdullah Hamzah; Darniati Darniati (Jurnal Medika Veterinaria, 2019)
The aims of this research was looked to determine the healing process of burns  Grade II B using a mixture of fresh and dried leaf kedondong with vaseline white rats (Rattus norvegicus). Animals used were 18 rats. This study was designed using three treatment groups namely (KI) vaseline, (KII) mixture of crushed leaves and fresh kedondong (KIII) mixture of crushed dried leaves kedondong and each two replications. Burns made on the backs of mice and the treatments are done twice a day for 21 days.Observation research parameter is the description of macroscopic and microscopic observed at day 7, 14, and 21 in the skin tissue with hematoxylin and eosin staining. The observation of macroscopic studies showed that the formation of a reddish color, presence of edema, and loss of the fastest consecutive scab is KI, KIII, and KII, while the formation of a scab fastest respectively KIII, KI and KII. The observation of histopathology showed on day 7, KI, KII and KIII found inflammatory cell infiltration, hemorrhage and edema with the spread of many.on the 14th day of KI and KII infiltration of inflammatory cells and their udema much, whereas KIII inflammatory cell infiltration decreased, and hyperemia increase, on the 21st day KI, KII and KII inflammatory cell infiltration, hyperemia and hemorrhage spread with a little, but KI and KII oedemanya still being spread. Based on the results of this study concluded that KIII accelerate the healing process of burns on rats